CD97 Promotes Tumor Aggressiveness Through the Traditional G Protein–Coupled Receptor–Mediated Signaling in Hepatocellular Carcinoma. Issue 5 (22nd September 2018) - Yin, Yin; Xu, Xiaoliang; Tang, Junwei; Zhang, Wenjie; Zhangyuan, Guangyan; Ji, Jie; Deng, Lei; Lu, Shuai; Zhuo, Han; Sun, Beicheng
Abstract : Cluster of differentiation 97 (CD97) is a member of the epidermal growth factor seven‐transmembrane family belonging to the class B G protein–coupled receptors (GPCRs). The protein affects tumor aggressiveness through its cellular ligand CD55 stimulation and exhibits adhesive properties. Studies have demonstrated the involvement of CD97 in dedifferentiation, migration, invasiveness, and metastasis of tumors. However, little information is currently available on the specific role of CD97 in hepatocellular carcinoma (HCC). Here, we have shown that CD97 up‐regulation in HCCs is positively correlated with tumor metastasis. Functionally, CD97 promoted cell migration and invasion in vitro . In an in vivo mouse model, overexpression of CD97 in HCC cells led to accelerated lung metastasis. Mechanistically, CD97 cooperated with the altered regulator, GPCR kinase 6 (GRK6), to mediate GPCR desensitization and internalization. Down‐regulation of GRK6 suppressed CD97 internalization and promoted CD97 expression. Integrated regulatory interactions between CD97 and GRK6 stimulated downstream matrix metalloproteinase 2/9 secretion and, consequently, HCC metastasis. Conclusion: Our collective findings support the utility of CD97 as an effective potential prognosticator and therapeutic target for HCC.